2022
DOI: 10.1111/jcmm.17492
|View full text |Cite
|
Sign up to set email alerts
|

Expression analysis of miRNA hsa‐let7b‐5p in naso‐oropharyngeal swabs of COVID‐19 patients supports its role in regulating ACE2 and DPP4 receptors

Abstract: Severe Acute Respiratory Syndrome Coronavirus‐2 (SARS‐CoV‐2) is the novel coronavirus responsible for worldwide coronavirus disease (COVID‐19). We previously observed that Angiotensin‐converting enzyme 2 (ACE2) and Dipeptidyl peptidase‐4 (DPP4) are significantly overexpressed in naso‐oropharyngeal swabs (NPS) of COVID‐19 patients, suggesting their putative functional role in the disease progression. ACE2 and DPP4 overexpression in COVID‐19 patients may be associated to epigenetic mechanism, such as miRNA diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 60 publications
(163 reference statements)
1
18
0
Order By: Relevance
“…Because we have demonstrated specific differences between PD and healthy control subjects, our study reveals the principal applicability of using oral and nasal swabs for biomarker testing in PD. In line, recent reports showed successful miRNA‐seq from such swabs 40,41 . Future studies using such material may support the development of useful biomarkers for neurodegenerative diseases on a larger scale.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Because we have demonstrated specific differences between PD and healthy control subjects, our study reveals the principal applicability of using oral and nasal swabs for biomarker testing in PD. In line, recent reports showed successful miRNA‐seq from such swabs 40,41 . Future studies using such material may support the development of useful biomarkers for neurodegenerative diseases on a larger scale.…”
Section: Discussionsupporting
confidence: 72%
“…In line, recent reports showed successful miRNAseq from such swabs. 40,41 Future studies using such material may support the development of useful biomarkers for neurodegenerative diseases on a larger scale.…”
Section: Discussionmentioning
confidence: 99%
“…Our data showed that 13 studies 53,54,56,57,66,[70][71][72][80][81][82][83]85 compared miRNA regulation in SARS-CoV-2 infected patients without further sub-staging of the disease severity, whereas 22 studies reported their results as an overall and also in sub-groups (Table 2). A total of 404 miRNAs were reported in these studies that showed significant dysregulation in infected patients.…”
Section: Mirna Dysregulation In "Inf Vs C" Studiesmentioning
confidence: 83%
“…Collected data showed that of these, most of the studies were published during the year 2021 ( n = 16), 53–68 followed by 2022 ( n = 15), 69–83 with the least numbers in the year 2020 ( n = 4) 53,84–87 (Figure 2a). Although the selected studies were published globally, most of them were reported from China ( n = 8), followed by Italy ( n = 7), Spain ( n = 4), and USA ( n = 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation